Paradigm of the Treatment of the Prophet's Mosque and the Current Mosque Through the Interpretation of Architectural Space in Social Reproduction - Salsa Syafiqa; Deni; Hendra A; Dela Andriani (Faculty of Engineering, Malikussaleh University, 2024)
From practical research, there are several references in academic ideas that contain thoughts to re-evaluate the shift in the treatment of mosques today compared to the Prophet's Mosque. The existence of mosques today practically prioritizes the provision of spiritual worship space capacity compared to social worship. So the architecture of the mosque as a place of worship that balances the relationship between humans and their God and the relationship between humans and humans is questioned. BKM as a generator of social reproduction of religious organizations that regulate the reality of mosque activities to improve the quality of the community becomes the object of analysis of architectural studies as the cause of the shift in treatment. Therefore, research was conducted through reference data from the Current Mosque and the Prophet's Mosque to analyze their performance through the idea of ​​structuring in order to reveal the problem of the paradigm shift in the treatment of the Current Mosque. The dialectic of BKM performance is used to test the extent to which the treatment of the Mosque adapts fantasy and fantastic ideas in the realm of architecture. The current mosque is more oriented towards social reproduction that strengthens activities over the relationship between humans and God, while the Prophet's Mosque in social reproduction has a balance to strengthen activities over the relationship between humans and God and the relationship between humans and humans.